Anti-gender campaigns in Europe - Kuhar, Roman,Paternotte, David (Rowman & Littlefield International, 2017)
This edited collection offers a transnational and comparative approach to understanding anti-gender mobilizations in Europe. Anti-Gender Campaigns in Europe – Contents – Abbreviations – 1
Includes bibliographical references and index. Description based on print version record
Keywords: Aufsatzsammlung; Sex discrimination–Europe; Sex discrimination; Europe; Homophobia; Europe; Transphobia; Europe; Electronic books; Homophobia; Sex discrimination; Transphobia; Europa